1994
DOI: 10.1038/bjc.1994.431
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis and childhood leukaemia/lymphoma: a population-based UKCCSG study

Abstract: Sm_mary There is a well-known raised risk of leukaemia in children with neurofibromatosis type 1 (NF-1).We carried out the first detailed population-based study of leukaemia and non-Hodgkin lymphoma (NHL) associated with NF-I in order to estimate the risk and elucidate the relationship between these conditions. Over the 17 year study period there were five cases of chronic myelomonocytic leukaemia (CMML) in patients with NF-1 (relative risk 221; 95% CI 71-514), 12 cases of acute lymphoblastic leukaemia (ALL) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
1
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(137 citation statements)
references
References 19 publications
5
126
1
5
Order By: Relevance
“…Sir -We read with interest the article on the increased risk for childhood leukaemias in neurofibromatosis (Stiller et al, 1994). This study confirmed the results of the first population-based study on the incidence of various malignant disorders in neurofibromatosis type 1 (NF-1) (Matsui et al, 1993).…”
supporting
confidence: 54%
“…Sir -We read with interest the article on the increased risk for childhood leukaemias in neurofibromatosis (Stiller et al, 1994). This study confirmed the results of the first population-based study on the incidence of various malignant disorders in neurofibromatosis type 1 (NF-1) (Matsui et al, 1993).…”
supporting
confidence: 54%
“…Other studies have reported an increased incidence of juvenile myelomonocytic leukaemia (JMML) in children with NF1 (Stiller et al, 1994). This malignancy has been reported to have an association with the presence of juvenile xanthogranulomas in this population.…”
Section: Discussionmentioning
confidence: 79%
“…Previous data have indicated overall additional malignancy risks in NF1 of between 5 and 15% (Sorensen et al, 1986;Huson et al, 1988;Baptiste et al, 1989;Matsui et al, 1993;Stiller et al, 1994;Friedman and Birch, 1997;Zoller et al, 1997;Evans et al, 2002), and these figures are commonly used when counselling patients; therefore, a more specific risk based on a larger study population would be useful. In addition, the advent of surveillance techniques for early detection and subsequent treatment of malignancy suggested that a more detailed analysis of the question of malignancy risk in NF1 was needed.…”
mentioning
confidence: 99%
“…They also emphasize the importance of searching for additional functions for the NF1 protein and of intensifying the screening for NF1 mutations in human lymphomas. An increased incidence of non-Hodgkin lymphoma has already been reported in NF1 patients (Stiller et al, 1994); however, the actual involvement of NF1 mutations in lymphomahgenesis, as in many other tumor types, remains still unknown because the large size of this gene has slowed down the process of screening for mutations other than large deletions or rearrangements.…”
Section: Mechanism Of Nf1 Tumor Suppressionmentioning
confidence: 99%
“…Mutations that inactivate the NF1 gene have been found in a variety of sporadic (Li et al, 1992;Andersen et al, 1993;Johnson et al, 1993) and neuro®bromatosis associated tumors (Legius et al, 1993;Stiller et al, 1994;Shen et al, 1996), including neuro®brosarcoma, pheochromocytoma, astrocytoma, neuroblastoma, melanoma, colon carcinoma, chronic myeloid leukemia, acute lymphoblastic leukemia and non-Hodgkin lymphoma. In addition to being mutated in tumors, Ras and NF1 are able to interact and function in the same proliferative pathway, suggesting a possible cooperating e ect for the deregulation of these two proteins in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%